A control of TiO2 nanostructures by hydrothermal condition and their application: a short review. (September 2019) - Hidayat, R; Fadillah, G; Wahyuningsih, S
Abstract: TiO2 (titanium dioxide) is an inorganic material that has many uses in various fields such as environment, sensor devices and solar energy conversion. Various method approaches have been developed for the synthesis of nanostructured TiO2, but the hydrothermal method is still considered the most effective method and provides many advantages in nanostructure formation because the methods can be controlled. In the present study, we will discuss the formation of TiO2 with various conditions on hydrothermal methods in TiO2 nanostructure formation. Generally, TiO2 nanoparticles can be obtained by hydrothermal methods. TiO2 precursors, pH, reaction time and also temperature are factors that influence the formation of TiO2 structures. The methods are commonly used because hydrothermal methods can easily control conditions to obtain a homogenous structure. The difference of TiO2 structure is very influential in its properties and activity performance.